PERAN PENDIDIKAN AGAMA BERBASIS MULTIKULTURAL DALAM MENGEMBANGKAN SIKAP INKLUSIF DAN KESADARAN BUDAYA SISWA - Azwar Rahmat; Rahmat Shodiqin (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to examine the role of multicultural-based religious education in developing inclusive attitudes and cultural awareness among students through a literature review method. Multicultural religious education is considered highly relevant in the context of Indonesia's diverse society, as it instils values of tolerance, respect for differences, and mutual respect among students from various cultural and religious backgrounds. The results of the literature review indicate that religious education that integrates multicultural principles can shape students' inclusive, open, and sensitive character towards social issues around them. Additionally, this education is also effective in enhancing students' cultural awareness, strengthening their self-identity, and fostering a harmonious and peaceful school environment. Thus, multicultural-based religious education is an important strategy in building a young generation that is tolerant, culturally aware, and ready to face the challenges of globalisation.